EMC for systems and installations - Williams, Tim, ....-; Armstrong, Keith, ....- (Oxford : Newnes, 2000)
This is a guide for the system designers and installers faced with the day-to-day issues of achieving EMC, and will be found valuable across a wide range of roles and sectors, including process control, manufacturing, medical, IT and building management. The EMC issues covered will also make this book essential reading for product manufacturers and suppliers - and highly relevant for managers as well as technical staff.
Keywords: Elektromagnetisme